Madness in the Archives: Anonymity, Ethics, and Mental Health History Research - Wright, David; Saucier, Renée (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
Historians have long been vexed by the challenges of using patient records as primary sources. Lurking behind the many methodological and interpretative challenges are ethical questions involving the status and identity of the dead patient. What rights do the deceased maintain over their medical records? What ethical obligations do researchers have in analyzing these historical records and, in particular, to preserving the anonymity of patients? Do professional duties diminish the further back one goes in time? Do patients suffering from mental distress differ from other “medical” patients in the ethical regard owed to them? Now that we know about the care of the mentally ill outside of formal institutions during the era of the asylum, is there something intrinsically different about the status of individuals once they entered formal institutions? Or do the designations of “lunacy” or “idiocy” on extramural death certificates or in census enumerators’ schedules oblige a similar professional discretion? Is the concern over confidentiality giving way to a new emphasis on returning names (and agency) to vulnerable groups in the past? This paper explores these questions, ones that lie at the heart of what we do as historians of disability, medicine, and society.